Pedagogical Competency Analysis in the Application of the E-A-S-I (Exposure - Analogy - Social Action - Impact Writing) Learning Model Based on Basic Literacy - Nenden Hendarsih; Dyah Lyesmaya; Ayi Abdurahman (Eastasouth Institute, 2026)
This study aims to evaluate and analyze teachers' pedagogical competence in implementing the E-A-S-I (Exposure, Analogy, Social Action, Impact Writing) learning model based on basic literacy at SDN Cipanengah, Sukabumi City. A qualitative approach with a case study design was used, involving five teachers from grades III to VI as participants. Data collection techniques included in-depth interviews, non-participant classroom observations, and document analysis of lesson plans and student artifacts. The findings indicate that although teachers successfully conceptualized and designed structured lesson plans that align with the student-centered approach, they faced substantial tactical obstacles during actual classroom practice. The main obstacles were identified at the Analogy and Impact Writing stages due to the deeply rooted teacher-centered paradigm and students' low critical reading and writing skills. Furthermore, spatial constraints and excessively large class sizes limited physical mobility during the Social Action stage. This study recommends a shift in teacher professional development from technical-procedural workshops to ongoing reflective mentoring and internal professional learning communities (Learning Studies) to foster strong teacher agency.